SUZANNA IVANIČ, Cosmos and Materiality in Early Modern Prague, Oxford 2021, Oxford University Press, 244 s., ISBN 978-0-19-289898-2 - Prchal Pavlíčková, Radmila (Dějiny – teorie – kritika, 2023)
Book review